2015
DOI: 10.1039/c4cp06078d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a nearby substrate on the reorganization energy of hole exchange between dye molecules

Abstract: A numerical method is presented to estimate the influence of a nearby substrate on the polarization energy and outer sphere reorganization energy (λ o ) for intermolecular hole transfer for a series of dye molecules. The calculation considers the net charge distribution of the oxidised molecule (determined from quantum chemical calculation of the highest occupied molecular orbital of the neutral molecule within the frozen orbital approximation) encapsulated within a conformal cavity, by the molecules total ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…More detailed consideration can be found in our earlier work. 25,26 Furthermore, we calculated λ i for a specific configuration of the dye molecules.…”
Section: Calculation Of the Reorganization Energy Of Hole Exchange Bementioning
confidence: 99%
“…More detailed consideration can be found in our earlier work. 25,26 Furthermore, we calculated λ i for a specific configuration of the dye molecules.…”
Section: Calculation Of the Reorganization Energy Of Hole Exchange Bementioning
confidence: 99%
“…Secondly, to account better knowledge about the height barrier of SEO, free energy of activation for the SEO was calculated using four-point method proposed by Nelsen (see SI). [52][53][54] We are convinced that this method result in a reasonable estimation of the electron transfer (ET) activation barrier. Thirdly, it has been reported that HFIP plays a critical role with oxidizing agent rather than with the radical cation formed.…”
Section: Mechanism Of Dimerizationmentioning
confidence: 99%
“…Secondly, to account better knowledge about the height barrier of SEO, free energy of activation for the SEO was calculated using four-point method proposed by Nelsen (see SI). [53][54][55] We are convinced that this method result in a reasonable estimation of the electron transfer (ET) activation barrier. Thirdly, it has been reported that HFIP plays a critical role with oxidizing agent rather than with the radical cation formed.…”
Section: Mechanism Of Dimerizationmentioning
confidence: 99%